Ab-initio study of (Ga, Cr)N and (Ga, Mn)N DMSs: under hydrostatic pressure. (14th March 2018) - Rani, Anita; Kumar, Ranjan
Abstract: The influence of hydrostatic pressure between 0–100 GPa on structural, electronic and magnetic properties of Crx Ga1−x N and Mnx Ga1−x N (x = 0.25) diluted magnetic semiconductors has been studied. The calculations have been performed using DFT as implemented in code SIESTA. LDA + U as exchange-correlation (XC) potential have been used to study the parameters. Under external pressure, shifting in both valence band and conduction band energy levels from their actual positions has been observed, which lead to modification of electronic properties. Also, N0 α, s-d exchange constant and p-d exchange constants, N0 β have been calculated at different pressures. Both the compounds show half metallic nature at studied pressure range.